Empatia e constituição da pessoa: uma abordagem fenomenológica da relação entre empatia e pessoa humana em Edith Stein - Carneiro, Lívia Rios (2021)
The empathy investigation to achieve the objectivity of the world led Stein to a strict study of the human individual development. From the analysis of the mechanisms of empathetic act in consciousness, something beyond the perception analyzed phenomenologically has come to light and was welcomed. The empathetic act processing is vital in Stein’s work, since the outcomes of this study gave rise to human being conception. Thereby, Stein developed her own philosophical anthropology, connecting phenomenology, classical metaphysics and her private involvement. Nowadays, several authors revisit Stein’s work in search of answers for the most thoughtful questions of our current time. The present essay is a qualitative research based on bibliographical survey, following the phenomenological method in the course of the human discovery.